Antitumor activity of the pachymic acid in nasopharyngeal carcinoma cells. (4th May 2017) - Zhang, Yan-Hua; Zhang, Yong; Li, Xiu-Ying; Feng, Xu-Dong; Jian, Wei; Li, Rong-Qing
ABSTRACT: Objective : To investigate the antitumour efficacy of pachymic acid (PA), which is a fungal extract component, on nasopharyngeal carcinoma (NPC) cells CNE-1, CNE-2.Methods : We have chosen NPC cell line CNE-2 for the study, and the cells were treated with PA before the detection. CCK-8 assay was used to detect the proliferative ability, and Annexin V-PI double staining was used for the detection of apoptosis rate; and the nucleus damage was detected by transmission electron microscope, the protein expression of the DNA damage pathway were detected by Western blot.Results : PA can significantly inhibited proliferation of CNE-1, CNE-2 cells. The proportion of apoptotic cells of all cell lines gradually increased in a dose-dependent manner induced by PA, P < 0.05. Meanwhile, the nucleus could be caused morphological changes and the expression of DNA damage-related proteins was upregulated by PA in CNE-2.Conclusions : PA can significantly inhibit cell proliferation and increase the apoptosis rates and may induce the apoptosis of the human NPC cells.